Dialogue : the mixed game - Weigand, Edda (Dialogue studies., 2010)
The 'Mixed Game Model' represents a holistic theory of dialogue which starts from human beings' competence-in-performance and describes how language is integrated in a general theory of human action and behaviour. Human beings are able to adapt to changing conditions and to pursue their interests by the integrated use of various communicative means, mainly verbal, perceptual and cognitive. The core unit is the dialogic action game or 'the mixed game' with human beings at the centre acting and reacting in cultural surroundings. The key to opening up the complex whole is human beings' nature. Th.